2014
DOI: 10.1002/ajmg.a.36859
|View full text |Cite
|
Sign up to set email alerts
|

Aortopathy in the 7q11.23 microduplication syndrome

Abstract: The 7q11.23 microduplication syndrome, caused by the reciprocal duplication of the WilliamsBeuren syndrome (WBS) deletion region, is a genomic disorder with an emerging clinical phenotype. Dysmorphic features, congenital anomalies, hypotonia, developmental delay highlighted by variable speech delay, and autistic features are characteristic findings. Congenital heart defects, most commonly patent ductus arteriosus, have been reported in a minority of cases.Included in the duplicated region is elastin (ELN), imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Subsequent FISH testing indicated that this child’s duplication corresponded to the classic WS deletion region (hereafter, classic Dup7). In the ensuing nine years, 30 children with classic Dup7 aged 6 months to 17 years have been described as part of case series [5 in Berg et al, 2007; 14 in van der Aa et al, 2009; 5 in Dixit et al, 2013; 6 in Parrott et al, 2015] and mean performance levels on various psychological assessments were reported by Sanders et al [2011] for four children with classic Dup7. In addition, 12 children with classic Dup7 were described in individual case reports [Somerville et al, 2005; Kriek et al, 2006; Depienne et al, 2007, 2009; Torniero et al, 2007; Merritt and Lindor, 2008; Orellana et al, 2008; Torniero et al, 2008; Malenfant et al, 2012; Değerliyurt et al, 2012; McGrew et al, 2012; Prontera et al, 2014; Zarate et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent FISH testing indicated that this child’s duplication corresponded to the classic WS deletion region (hereafter, classic Dup7). In the ensuing nine years, 30 children with classic Dup7 aged 6 months to 17 years have been described as part of case series [5 in Berg et al, 2007; 14 in van der Aa et al, 2009; 5 in Dixit et al, 2013; 6 in Parrott et al, 2015] and mean performance levels on various psychological assessments were reported by Sanders et al [2011] for four children with classic Dup7. In addition, 12 children with classic Dup7 were described in individual case reports [Somerville et al, 2005; Kriek et al, 2006; Depienne et al, 2007, 2009; Torniero et al, 2007; Merritt and Lindor, 2008; Orellana et al, 2008; Torniero et al, 2008; Malenfant et al, 2012; Değerliyurt et al, 2012; McGrew et al, 2012; Prontera et al, 2014; Zarate et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen adults with classic Dup7 also were included in case series or individual case reports. Two individuals (aged 19 and 23 years) were probands [Berg et al, 2007; Kirchhoff et al, 2007]; the remaining 11 had one or more children with classic Dup7 and were identified primarily by cascade testing [2 in Berg et al, 2007; 1 in Merritt and Lindor, 2008; 1 in Torniero et al, 2008; 6 in van der Aa et al, 2009; 1 in Parrott et al, 2015]. Several additional individuals with larger or smaller duplications of 7q11.23 have been included in some of the case series.…”
Section: Introductionmentioning
confidence: 99%
“…In this population some of the diagnoses included major aneuploidies that should be easily [6][7][8][18][19][20][21][22][23][24][25] In many cases, in spite of lacking further supporting clinical evidence of a direct link between AoD and the genes involved in the remaining patients with cytogenetic abnormalities, other potential candidate genes with relationships to cardiac morphogenesis or pathology were identified ( Table 3). [26][27][28][29][30][31][32][33][34][35] We also were able to identify other less common genetic conditions in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Most duplication carrier parents showed a history of learning difficulties and/or language delay but were employed and functioning well in adult life 23 24. Due to the finding of cardiac defects and aortopathy in a subset of individuals, cardiovascular surveillance has been recommended for these patients 26. Minor dysmorphic features, neonatal hypotonia, various brain anomalies, cleft palate, epilepsy, cryptorchidism, joint laxity, attention-deficit hyperactivity disorder (ADHD) and autistic features have also been reported in some individuals 23 27.…”
Section: Methodsmentioning
confidence: 99%